Aplikasi Model Diplomasi Ekonomi Indonesia terhadap Brasil dalam Meningkatkan Ekspor Minyak Nabati Periode 2017-2021 - Annef, Al Bahits; Darmastuti, Shanti; Kurniawan, Andi (Indonesian Perspective, 2022)
This paper mainly tries to explore the new Model of Indonesian Economic Diplomacy to Non-Traditional Market by Setiawan & Sulastri (2020) with a study case of increasing vegetable oil export to Brazil. Brazil is one of the main targets of Indonesia’s export-development policy to non-traditional markets. The main concern of this paper is how economic diplomacy plays a role in reacting to the declining trend of vegetable oil exports as Indonesia’s leading export product to Brazil during 2016-2020. This paper is a descriptive qualitative research using simple trade calculations to justify Indonesian exports orientation. This paper found there are at least 6 driving factors for the implementation of economic diplomacy, 3 prominent actors for conducting economic diplomacy and 8 processes of economic diplomacy. Indonesia has successfully increased the export trend of vegetable oil to Brazil in the period of 2017-2021, however specific economic diplomacy efforts to encourage vegetable oil exports were identified as minimum.